A COGNITIVE STYLISTIC ANALYSIS OF LEWIS CAPALDI'S SONG “SOMEONE YOU LOVED” - Simanjuntak, Windy Octalin; Saragih, Silvia Efani; Manurung, Rifdah Aatikah; Sihotang, Tiarma; Alivia, Cut Putri; Rangkuti, Rahmadsyah (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
Cognitive stylistics is a branch of linguistics that focuses on the study of how language and literature interact with human cognition and mental processes. This study presents a cognitive stylistic analysis of Lewis Capaldi's song "Someone You Loved." This study aims to explore the cognitive processes and stylistic features employed in the song's lyrics. This research uses a descriptive qualitative method by focusing on, highlighting, and analyzing each lyric in the song. The results of this study show the coherence among figures of speech used in the song. In conclusion, this study contributes to understanding how cognitive processes and stylistic choices intertwine in constructing emotional narratives within song lyrics.